Uji Aktivitas Antioksidan Ekstrak Daun Patikan Kebo (Euphorbia hirta L.) - Karim, Karina; Jura, Minarni Rama; Sabang, Sri Mulyani (Universitas Tadulako, 2015)
Patikan kebo (euphorbia hirta L.) is a plant commonly found in the tropical regions. The objectiveof this research was to determine the antioxidant activity of Patikan kebo leaves extract and tocategorize the strength of the extract in blocking free radicals. This research was conducted by laboratoryexperiment using maceration extraction techniques. Antioxidant activity of the extract was tested using1,1-diphenyl-2-pikrilhidrazil (DPPH). Variation concentrations of the used of Patikan kebo leavesextract and vitamin c as a positive control used for analysis were of 20 ppm, 40 ppm, 60 ppm, and 80ppm. Analysis of the sample was conducted using spectronic UV-Vis. The result showed that Patikankebo leaves extract was a very strong antioxidant. It was proved by the number of IC50 less then 50. Thecalculation of IC50 of patikan kebo leaves extract was 11.50 mg/L.